2007
DOI: 10.1080/07481180701490743
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender, and Living Circumstances: Discriminating Older Adults on Death Anxiety

Abstract: The present study examines the effect of age, gender, and living circumstances on elderly persons' death anxiety. For this purpose, 299 persons attending public parks (average age = 70 years) were interviewed using the Death Anxiety Survey Schedule, which is a set of 10 questions related to death anxiety from an Indian perspective. Women, those relatively older, and those living with family were significantly more anxious about the word death. The gender and age results in this Indian sample are similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
(16 reference statements)
1
26
0
4
Order By: Relevance
“…Abdel-Khalek and Al-Kandari found Kuwaiti middle-aged women had a significantly higher mean ASDA total score also on 17 out of 20 items of the scale [26]. On the Death Anxiety Survey Schedule from an Indian perspective, Madnawat and Kachhawa indicated that women were significantly more anxious about the word of death [32]. Abdel-Khalek et al found that, on the ASDA, Egyptian, Kuwaiti, Lebanese, Syrian, Spanish, and American women (no English women) had significant higher mean scores than men [29].…”
Section: Discussionmentioning
confidence: 99%
“…Abdel-Khalek and Al-Kandari found Kuwaiti middle-aged women had a significantly higher mean ASDA total score also on 17 out of 20 items of the scale [26]. On the Death Anxiety Survey Schedule from an Indian perspective, Madnawat and Kachhawa indicated that women were significantly more anxious about the word of death [32]. Abdel-Khalek et al found that, on the ASDA, Egyptian, Kuwaiti, Lebanese, Syrian, Spanish, and American women (no English women) had significant higher mean scores than men [29].…”
Section: Discussionmentioning
confidence: 99%
“…Women may also have different sociocultural experiences and cultural conditioning than men. For example, studies have found that female gender has been associated with higher death anxiety in adolescent populations and in cross-cultural research (Adbel-Khalek, 1991, 2005Cotter, 2003;Pierce, 2007;Singh Madnawat, & Singh Kachhawa, 2007). In a large sample of older individuals aged 61 to 80 years, elderly females were shown to have significantly higher death anxiety than males (Hickson, Housley, & Boyle, 1988).…”
Section: Attributes Of Death Anxietymentioning
confidence: 94%
“…Likewise, in the study made by Akca and Kose, the death anxiety levels of women were found to be higher than men (Akca and Kose, 2008). Madnawat et al reported that the death anxiety increases with age in women (Madnawat and Kachhawa, 2007). Similiarly, in the study made by Tang, Wu and Yan (2002), they were found that the death anxiety scores of the female university students were higher than the male ones (Ayten, 2009;.…”
Section: 2405 Factors Affecting the Death Anxiety Levels Of The Relamentioning
confidence: 80%